Foot contact angle variability during a prolonged run with relation to injury history and habitual foot strike pattern - Paquette, M. R.; Milner, C. E.; Melcher, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Foot strike pattern and movement variability have each been associated with running injuries. Foot contact angle (FCA) is a common measure of strike pattern. Thus, variability in FCA could be an important running injury risk factor. The purposes of this study were to compare (a) foot contact angle (FCA) and its variability between runners with and without injury history and, (b) FCA variability between habitual rearfoot strike (RFS) and non-RFS runners during a prolonged run. Twenty-three runners with and 21 without injury history participated. Motion capture was used to collect kinematic data during a 40 min treadmill run. Average FCA and its variability were compared between injury groups and among four time points. FCA and its variability were not different between runners with and without injury history or among time points during the run. FCA variability was lower in non-RFS compared to RFS runners (P < 0.001). Lower FCA variability in non-RFS runners may have implications for higher injury risks due to repeated localized tissue loading. Prospective analyses on the effects of lower FCA variability on injury risk are needed.